Loss of parish-priest’s office - WROCEŃSKI, JÓZEF (Prawo Kanoniczne, 2020)
The pastoral care for the community of the faithful entrusted to parish-priest is essentially connected with the office of the pastor. This means that the parish priest is called to fulfill his mission because of his participation in the priesthood of Christ and the office entrusted to him by the bishop. Therefore, he performs this office not autonomously and without any dependence, but under the authority of the diocesan bishop, who, by virtue of God's law, is a shepherd of the particular Church. For the sake of the faithful, the church legislator foresees several ways of losing the office of parish priest. The author in this article discusses this very complex issue. Based on general norms, the church office, including the office of a parish priest, is lost after the lapse of time, after reaching the legal age, because of resignation, transfer, removal and deprivation. The natural reason for the loss of every church office is the death of the person holding it. Despite these provisions, the church legislator for the office of the parish priest separately determines the ways of loss, including the removal or transfer made in accordance with the law, waiver for a just cause and the passage of time. Particularly in the event of removal or transfer, it provides for special administrative procedures. The separation of these two procedures is primarily due to the important role that the parish priest has to fulfill in the life of the church community and the fact of the durability of his office. The role of these procedures is elimination of the possible abuses by the priest, which could deprive the parishioners of the spiritual goods to which they are entitled, without omitting the good of the priest. All ways of losing the office of parish priest, apart from the particular effects specified by the legislator, result in the vacancy of the parish.